(untitled) (LEARNing Landscapes, 2016)
This narrative re ects on the artist’s involvement in two separate community-engaged art projects: a public event created to memorialize the dead and a digital storytelling project at a Seniors Centre in North Vancouver, B.C. Through a personal arts-based inquiry into ritual and memory, the two projects merge and begin to inform the artist’s work with seniors. The inquiry helps to deepen a sense of shared community and to de ne what a genuine community-engaged practice may be. This article inquires into why art matters in community-engaged work and how creative practice can create new structures of learning and deepen bonds within community.